Analysis of Shelf Type Flash Dryer Machine in the Process of Drying Purple Leaves (Graptophylum pictum Griff) - Nurwahyuningsih, Nurwahyuningsih; Rakhmadevi, Ade Galuh; Fadhila, Putu Tessa; Djamila, Siti; Wanta, Firman Dwi (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Purple leaves (Graptophyllum pictum L griff) is a plant that has many benefits. People generally use purple leaves plants as herbal plants. The part of this plant that is often used is the leaves. Various kinds of processed purple leaf products have been developed, one of which is a purple leaf herbal drink that can be brewed like tea. In the manufacture of these products, a purple leaves drying process is required, namely the process of reducing the moisture content of the wet material to a certain moisture content value. The use of a dryer is able to speed up the drying process, not dependent to the weather, quality guarantee, more hygienic product, homogenic result, and it does not require a large area. In this study, a rack-type flash dryer was used with LPG fuel and added a fan to obtain a forced convection effect, in which hot air is circulated evenly by the fan in the drying chamber. The purpose of this study is to determine the effect of temperature distribution in the drying chamber, calculate the efficiency of the drying machine, and determine the final moisture content of the material from the drying process. The conclusion of this study shows that the flash dryer is very efficient in the process of drying purple leaves, the lowest water content is found on shelf 2 (middle part) with an average of 7.47% with a large amount of energy used of 38,246.55 kJ. And the efficiency of the dryer reaches 90.62%. The temperature distribution that occurs in the drying chamber for 4 hours of the drying process is quite even and has an average temperature of 50oC.